Análise da produtividade de uma pequena empresa de recapadora de pneus - Ogasawara, Dominique Takaessu (2023)
Knowing a company's productivity is a key factor in making better use of its resources. This work carried out a study to measure some aspects of the operational efficiency of a tire retreading company. Several stages of collecting company data were carried out to measure the company's capacity, idleness, availability, and productivity. Subsequently, the most significant losses were identified and, finally, suggestions for improvement were made, according to the calculated indicators. It was possible to conclude that the biggest loss is the capacity of the Autoclave Machine, this loss can be mitigated by increasing the workload of workers in the bottleneck resources. Another possible improvement to be applied is the rotation of work to reduce worker idleness, in addition to seeking to balance production through planning that is better distributed over time.